New HIV diagnoses among adults aged 50 years or older in 31 European countries, 2004–15: an analysis of surveillance data - Tavoschi, Lara (2018)
EU/EEA HIV Surveillance Network: Daniela Schmid, André Sasse, Dominique Van Beckhoven, Tonka Varleva, Tatjana Nemeth Blazic, Linos Hadjihannas, Maria Koliou, Marek Maly, Susan Cowan, Kristi Rüütel, Kirsi Liitsola, Mika Salminen, Françoise Cazein, Josiane Pillonel, Florence Lot, Barbara Gunsenheimer-Bartmeyer, Stavros Patrinos, Dimitra Paraskeva, Maria Dudas, Haraldur Briem, Gudrun Sigmundsdottir, Derval Igoe, Kate O'Donnell, Darina O'Flanagan, Barbara Suligoi, Šarlote Konova, Sabine Erne, Irma Caplinskiene, Aurélie Fischer, Jackie Maistre Melillo, Tanya Melillo, Eline Op de Coul, Hans Blystad, Magdalena Rosinska, Isabel Aldir, Helena Cortes Martins, Mariana Mardarescu, Peter Truska, Irena Klavs, Asunción Díaz, Maria Axelsson, Valerie Delpech